The Effect of Intellectual Capital, Firm Size and Leverage on Financial Performance Moderated by Competitive Advantage - Anggraeni Rinjani, Mandalike; Tuffahati, Nabila; Silvia Mandang, Dhea; Yulianto, Agung (Journal of Accounting and Finance Management, 2025)
This research seeks to examine how competitive advantage moderates the effect of intellectual capital, firm size, and leverage on financial performance. The quantitative study examines Indonesia Stock Exchange-listed food and beverage subsector manufacturers from 2020 to 2023. Based on the researcher's criteria, 32 food and beverage subsector manufacturing enterprises were sampled for four years using purposive sampling. From this era, 128 research data were collected. The analysis was conducted using Eviews 12 software with the Fixed Effect Model (FEM) approach using Indonesia Stock Exchange-obtained yearly financial statement. This study shows that firm size and leverage affects financial performance, but intellectual capital does not. Competitive advantage moderates firm size size and leverage on financial performance. Competitive advantage cannot moderate the intellectual capital-financial performance connection.